Pyrolyzed human hair: a review on synthesis, characterization and applications - Bhandari, Tika Ram; Lamsal, Bidit; Adhikari, Rameshwar (BIBECHANA, 2021)
Human hair, a common biowaste, can be pyrolyzed to prepare many kinds of functional materials. Pyrolyzed hair has been used in various forms of traditional medicine, sensor, ink, and electrolytes. This review highlights the major structural characteristics of human hair and its pyrolyzed form. It also addresses the characterization techniques used for the structure elucidation of pyrolyzed human hair as well as its potential applications. BIBECHANA 18 (1) (2021) 231-239